A Social Accounting Perspective for Institutional Transformation and Resource Management in the AI-Based Financial Sector - Nicholas Renaldo; Teddy Chandra; Achmad Tavip Junaedi; Harry Patuan Panjaitan; Jahrizal Jahrizal (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
The primary purpose of this research is to explore the role of social accounting in managing institutional arrangements and resource allocation in the AI-based financial sector. The study follows a descriptive-exploratory design, aiming to investigate and describe the various aspects of AI adoption in the financial sector. The research will also examine how social accounting frameworks can be adapted to assess the broader impacts of AI. The findings suggest that while AI has the potential to enhance efficiency, innovation, and competitiveness within the financial sector, its adoption raises significant challenges. Financial institutions must undergo institutional restructuring to align with regulatory expectations and ensure transparent, ethical AI practices. Financial institutions must adapt their governance models to incorporate AI technologies while ensuring transparency, accountability, and ethical compliance. Future research should expand the scope of this study by including a larger and more diverse sample of financial institutions globally.